Клінічний випадок діагностики та лікування хворого з АКТГ-ектопічним синдромом - Черенько, С. М.; Гетьман, В. Г.; Линчевський, О. В.; Нечай, О. П.; Щекатурова, Л. В. (Clinical Endocrinology and Endocrine Surgery, 2012)
Ectopic ACTH syndrome is a variant of hypercorticism due to ectopic production of ACTH by tumors of endocrine glands or by non-endocrine organs and tissues. It presents 1 -2% of all cases of Cushing's syndrome. The case of successful diagnosis and treatment of ectopic ACTH syndrome, of multiply small neuroendocrine thymus tumors origin, has been presented in the paper.